Heavy metal determination of shark Scoliodon laticaudus in Johor waters - Yap, Chee Kong; Ong, Meng Chuan; Ng, Yenlin Erin; Ghazali, Adiana; Ravikumar, Lavannia; Takarina, Noverita Dian (Malaysian Analytical Sciences Society, 2024)
The sharks from Johor waters were investigated to evaluate certain heavy metal concentrations and their potential human health concerns. This study obtained 25 Scoliodon laticaudus as bycatches from the local fishermen’s market in Johor and stored them at a low temperature before further analysis. The sharks were divided into gill, muscle, fin, stomach, and liver samples with oven drying at 60°C. Certain heavy metals (As, Cd, Cr, Cu, Fe, Hg, Pb, and Zn) were then evaluated using an Inductively Coupled Plasma Mass Spectrometer (ICP-MS) after the digestion process using nitric acid (HNO3). This study presented the ascending metal concentration sequences as Fe > Cd > Hg > Pb > Cr > As > Cu > Zn for livers, Cd > Hg > Fe > Pb > Cr > As > Cu > Zn for stomach linings, Cd < Hg < Pb < Fe < Cr < Cu < As < Zn for fins, Hg < Cd < Fe < Pb < Cr < Cu < As < Zn for gills, and Cd < Hg < Fe < Pb < Cr < Cu < As < Zn for muscles. Therefore, the average pollutant load indexes (PLIs) (contamination levels) for livers, stomach linings, fins, gills, and muscles were 3.31, 2.23, 3.15, 2.47, and 3.35, respectively. Based on the PLI values, this study successfully indicated a moderately polluted contamination level.